Pemanfaatan Limbah Anorganik untuk Revitalisasi Kebun Toga dan Gizi di Desa Kebumen - Stanislaus, Sugiyarta; Diasmika Ardhy, Handy; Kirana, Diva; Gilang Exfanto, Tanjung; Sapitri, Tiana (Universitas Negeri Semarang, 2024)
Kebumen Village, Banyubiru District, Semarang Regency faces challenges in managing inorganic waste, particularly plastic, and the need to enhance the use of medicinal plants (TOGA) for community health. The program